Gender Differences in Completed Schooling - Charles, Kerwin Kofi; Luoh, Ming-Ching (The Review of Economics and Statistics, 2003)
This paper summarizes the dramatic changes in relative educational attainment by men and women over the past three decades. Stock measures of education among the entire adult population show rising attainment levels for both men and women, with men enjoying an advantage in schooling levels throughout this interval. Cohort-specific analysis reveals that these stock measures mask two interesting patterns: (a) gender difference at the cohort level had vanished by the early 1950 birth cohort and has been reversed in sign ever since; (b) for several cohorts, attainment rates were flat for women and flat and falling for men. This last is puzzling in the face of the large college premia that these cohorts observed when making their schooling choices. We present a simple human capital model showing how the anticipated dispersion of future wages should affect educational investment, and find that a model which includes measures of future earnings dispersion fits the data for relative schooling patterns quite well.